Store Attributes and Experience Quality Affect Loyalty: Evidence from Muslim Fashion Retail - Lubaba, Hanny (Jurnal Ilmu Manajemen Advantage, 2025)
This study aims to examine the relationship between store attributes and customer loyalty, with experience quality as a mediating variable in the Muslim fashion retail industry in Indonesia. The research adopts a quantitative approach, testing both direct and indirect effects through a mediation model. Data were collected from 110 customers of Ahwarumi Fashion, a Muslim fashion retail company located in Lamongan Regency. The study investigates how store attributes, comprising product variety, pricing, service quality, and store atmosphere, influence customer loyalty, and whether experience quality enhances or mediates this relationship. The findings are expected to provide empirical evidence supporting the theoretical linkage between store attributes and customer loyalty and to clarify the role of experience quality as a key determinant in retail marketing. The study contributes to the literature by extending prior research that primarily examined these constructs independently, offering a more integrated model of retail customer behaviour. From a managerial perspective, the results are anticipated to guide fashion retailers in designing customer-centric strategies that emphasise the importance of store attributes and experiential Quality in strengthening long-term customer loyalty.